Performance of Mumps PCR and Serologic Testing During a University-Associated Mumps Outbreak in Charleston, SC. (October 2020) - Stoltz, Kristen; Puri, Shruti; Curry, Scott
Abstract : Background: Sensitive diagnostic testing is critical in responses to mumps outbreaks. PCR testing of buccal swabs is the most sensitive diagnostic test, but IgM serology remains standard in much of the United States. We provided testing guidance stressing use of mumps PCR to ambulatory clinics and emergency departments in addition to the standard serologic testing for acute mumps beginning in 2018. We compared the performance of PCR and IgM serology to assess cases of parotitis presenting during a community outbreak of mumps in fall 2019 associated with a university in Charleston, SC. Methods: All patients tested for mumps who presented to our facility (ER and ambulatory clinics) with mumps PCR and/or mumps IgM ordered between September 2019 and January 2020 were included. Mumps PCRs were sent to a commercial reference laboratory (ARUP). Confirmed cases were defined as having a positive mumps PCR and/or IgM with parotitis. Clinical characteristics of mumps patients including age, duration of symptoms, MMR history, and association with the university were obtained by chart review. Results: Mumps was confirmed in 15 of 44 tested patients (34%), with 15 of 15 mumps patients (100%) having positive PCR and 1 of 15 patients (7%) and 1 of 15 patients (7%) having positive and equivocal mumps IgM serologies, respectively. Only 1 patient who did not meet our mumps case definition (no CT imaging evidence of parotitis, no fevers, chronic sinus symptoms) had a positive PCR and had recent receipt of a third MMR dose in response to the ongoing outbreak. Median age for mumps patients was 22 years (range, 15–48) with 8 of 15 cases (53%) detected among university students and an additional 2 cases having close connections to the university associated with the outbreak. Only 1 of 15 mumps patients (6.7%) was febrile at presentation (median temperature, 37.2°C) and mumps cases presented for testing ≤3 days for 7 of 15 cases (47%) (range, 0–13 days from symptom onset). No cases were diagnosed by IgM only, and 10 of 15 mumps cases had some recollection of remote MMR immunization, whereas 6 of 15 (40%) had 2 documented MMR doses at <5 years of age. Conclusion: Serologic IgM testing for diagnosis of mumps appears insensitive for detection of cases in outbreaks within highly immunized adult patients. Although our recommended shift to PCR likely enhanced case finding during this outbreak, the potential for false-positive PCRs due to vaccine strain shedding following third-dose MMR immunization may also be considered a threat to the specificity of the test during outbreak situations. Funding: None Disclosures: None